Transcriptomic, epigenomic, and neuroanatomic signatures differ in chronic prurigo, atopic dermatitis, and brachioradial pruritus - Agelopoulos, Konstantin; Renkhold, Lina; Wiegmann, Henning; Dugas, Martin; Süer, Aysenur; Zeidler, Claudia; Schmelz, Martin; Pereira, Manuel P.; Ständer, Sonja (The journal of investigative dermatology, 2023)
Scratching and scratch-induced injuries, including neuroanatomical alterations, are key characteristics of chronic pruritus entities of different origins. The aim of this study was to link gene expression (array hybridization, qPCR) with DNA methylation (array hybridization) and neuroanatomy (PGP9.5 staining) in chronic nodular prurigo (CNPG), atopic dermatitis (AD), brachioradial pruritus (BRP), and matched healthy controls. Specific signatures of gene expression and DNA methylation clearly discriminated pruritic lesional skin from nonpruritic skin in CNPG and from healthy skin of volunteers, respectively. Although intraepidermal nerve fiber density was indiscriminately reduced, the level of epidermal branching, assessed by a semiquantitative pattern analysis, differentiated the entities (CNPG > BRP > AD). Correspondingly, repellent SEMA3A showed the highest expression in AD, whereas axonal growth-promoting nerve GF was most prominent in CNPG and BRP. Overexpression of genes for nerve fiber regeneration (NELL2/NFKB/ARTN) was found in AD and CNPG but not in BRP. Our findings suggest that differential branching patterns rather than mere innervation density separate chronic itch conditions and reflect disease-specific local expression profiles. In pruritic dermatoses (AD and CNPG), nerve injury and subsequent sprouting may primarily result from chronic scratching, whereas genuine neuropathy is expected to underlie BRP.
Online veröffentlicht: 6. September 2022, korrigiert veröffentlicht: 4. Oktober 2022
Gesehen am 31.03.2023